Comparison of methods (ROV, diver) used to estimate the composition and abundance of biota colonizing an offshore oil platform: A pilot study - Ann Scarborough Bull; Mary M. Nishimoto; Milton S. Love; Scott Clark; Katelin Seeto; Merit McCrea; Charin Park; Li Kui; Conner Jainese; Azivy Aziz; Jordan Angle (Continental Shelf Research, 2023)

Combining surface and soil environmental DNA with artificial cover objects to improve terrestrial reptile survey detection - Kathleen E. Kyle; Michael C. Allen; Jeffrey Dragon; John F. Bunnell; Howard K. Reinert; Robert Zappalorti; Benjamin D. Jaffe; Jordan C. Angle; Julie L. Lockwood (Conservation Biology, 2022)
Reptiles are increasingly of conservation concern due to their susceptibility to habitat loss, emerging disease, and harvest in the wildlife trade. However, reptile populations are often difficult to monitor given the frequency of crypsis in their life history. This difficulty has left uncertain the conservation status of many species and the efficacy of conservation actions unknown. Environmental DNA (eDNA) surveys consistently elevate the detection rate of species they are designed to monitor, and while their use is promising for terrestrial reptile conservation, successes in developing such surveys have been sparse. We tested the degree to which inclusion of surface and soil eDNA sampling into conventional artificial‐cover methods elevates the detection probability of a small, cryptic terrestrial lizard, Scincella lateralis . The eDNA sampling of cover object surfaces with paint rollers elevated per sample detection probabilities for this species 4–16 times compared with visual surveys alone. We readily detected S. lateralis eDNA under cover objects up to 2 weeks after the last visual detection, and at some cover objects where no S. lateralis were visually observed in prior months. With sufficient sampling intensity, eDNA testing of soil under cover objects produced comparable per sample detection probabilities as roller surface methods. Our results suggest that combining eDNA and cover object methods can considerably increase the detection power of reptile monitoring programs, allowing more accurate estimates of population size, detection of temporal and spatial changes in habitat use, and tracking success of restoration efforts. Further research into the deposition and decay rates of reptile eDNA under cover objects, as well as tailored protocols for different species and habitats, is needed to bring the technique into widespread use.

High‐resolution sequencing reveals unexplored archaeal diversity in freshwater wetland soils - Adrienne B. Narrowe; Jordan C. Angle; Rebecca A. Daly; Kay C. Stefanik; Kelly C. Wrighton; Christopher S. Miller (Environmental Microbiology, 2017)
Summary Despite being key contributors to biogeochemical processes, archaea are frequently outnumbered by bacteria, and consequently are underrepresented in combined molecular surveys. Here, we demonstrate an approach to concurrently survey the archaea alongside the bacteria with high‐resolution 16S rRNA gene sequencing, linking these community data to geochemical parameters. We applied this integrated analysis to hydric soils sampled across a model methane‐emitting freshwater wetland. Geochemical profiles, archaeal communities, and bacterial communities were independently correlated with soil depth and water cover. Centimeters of soil depth and corresponding geochemical shifts consistently affected microbial community structure more than hundreds of meters of lateral distance. Methanogens with diverse metabolisms were detected across the wetland, but displayed surprising OTU‐level partitioning by depth. Candidatus Methanoperedens spp. archaea thought to perform anaerobic oxidation of methane linked to iron reduction were abundant. Domain‐specific sequencing also revealed unexpectedly diverse non‐methane‐cycling archaeal members. OTUs within the underexplored Woesearchaeota and Bathyarchaeota were prevalent across the wetland, with subgroups and individual OTUs exhibiting distinct occupancy and abundance distributions aligned with environmental gradients. This study adds to our understanding of ecological range for key archaeal taxa in a model freshwater wetland, and links these taxa and individual OTUs to hypotheses about processes governing biogeochemical cycling.